Transmission scheme and capacity analysis of onboard multi-antenna system in high-speed train - Wan-tuan LUO; Xu-ming FANG; Meng CHENG; Xiang-juan ZHOU (Tongxin xuebao)
Based on the three-dimensional modeling of line-of-sight SIMO (single-input multiple-output) channel for high-speed railway, which adopts uniform linear receiving array, the channel capacity of N -group receiving arrays was analyzed. The combining capacity grows but vibrates near base station and falls to Shannon capacity quickly. Instead of increasing group numbers of receiving arrays simply, stable capacity can be obtained by adjusting array parameters, grouping arrays and changing array weights among groups. The computer simulation results illustrate that proper setting would get stable channel capacity and avoid oscillation when the train is passing through the base stations.